Features of Formation of Residential Architecture of Yerevan City in New Socio - Economic Conditions - Khachatryan, Tagush; Babajanyan, Grigor (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The relevance of the study caused changes in the compositional-spatial structure of Yerevan, the theory of which was the loss of monuments of historical and cultural heritage, and the originality of the appearance of the city. The purpose of the study is to analyze the current structure of Yerevan in modern conditions. In the process of analysis and based on the results of the field survey, the stages of development of residential architecture for the period of 1990-2020 were identified and scientifically defined, as well as parallels were drawn between the metamorphoses of existing buildings and the formation of new residential units. The factors influencing the development trends of residential architecture in Yerevan have been studied, and a chronological division of the above-mentioned processes into stages has been proposed, taking into account the characteristic features of each of them. Conclusions: the research material can become the basis for the formation of principles for preserving the original appearance of Yerevan.